Probing electromechanical behaviors by datacube piezoresponse force microscopy in ambient and aqueous environments. (21st March 2019) - Cui, Anyang; Wolf, Peter De; Ye, Yan; Hu, Zhigao; Dujardin, Antoine; Huang, Zhuangqun; Jiang, Kai; Shang, Liyan; Ye, Ming; Sun, Hao; Chu, Junhao
Abstract: For assisting the in-depth investigations of widespread electromechanical phenomena in functional materials, piezoresponse force microscopy (PFM) has gradually evolved to realize full information-flow acquisition and fit the conductive liquid working environments. Here, we designed data cube (DCUBE) based PFM to collect the electromechanical effect into a high-dimensional array of piezoresponse by adding ac bias with a wide range of frequencies to the probe. The electromechanical and mechanical spectra can be consecutively extracted at each pixel in the intermittent-contact mode. High-resolution ferroelectric domains of the poled LiNbO3 were mapped, corresponding to the ideal phase contrasts of about 180° in air, decane, and deionized water. Rich information detection and non-contact mode in DCUBE-PFM bring many merits on the electromechanical characterizations, especially for elastic-inhomogeneous surfaces and soft materials. Moreover, we systematically reveal the Debye screening effect and time-resolved field-oriented ion dynamics, which play crucial roles in the reduction of PFM spatial resolution in electrolytes. These physical discussions provide strategies to further realize high-resolution electromechanical imaging in highly conductive liquid environments.